A cautionary approach to adult female groin swelling: hydrocoele of the canal of Nuck with a review of the literature. (17th March 2016) - Patnam, Varun; Narayanan, Ramakrishna; Kudva, Annappa
Abstract : Hydrocoele of the canal of Nuck in an adult female is a rare entity and analogous to hydrocoele in males. Its usual presentation is in children, and its occurrence in adults is very uncommon, more so of the hour-glass variety. We report a case of a 38-year-old woman presenting with a right inguinal swelling of 3-month duration. On physical examination, the swelling was non-tender, cystic and irreducible. There was no cough impulse. Ultrasonography and contrast-enhanced CT revealed a cystic swelling with clear contents in the right inguinal region. Surgery was performed with excision of the cyst. The histopathology report suggested flat mesothelium cells, confirming the diagnosis.